Salafism and Traditionalism Scholarly Authority in Modern Islam - Hamdeh, Emad 1984- (New York University of Cambridge ESOL Examinations, 2021)
Provides a detailed reconstruction of the heated debates between Salafis and Traditionalist over the contested role of Islamic scholarly authority.
Cover -- Half-title -- Title page -- Copyright information -- Dedication -- Epigraph -- Contents -- Acknowledgments -- Introduction -- Part I History -- 1 Traditionalism and Salafism -- Islamic Modernism -- Contemporary Modernists -- Traditionalism -- Salafism -- Purist Salafism -- Albani and Modernists -- Albani and the Spread of Salafism -- Literalism -- 2 A Controversial Salafi -- Albani's Formative Years -- Clashing with Saudi Salafis at the University of Medina -- Impact on the Saudi Religious Landscape -- The Muslim Brotherhood -- Traditionalist Detractors of Salafism -- 3 Gatekeepers of Knowledge: Self-Learning and Islamic Expertise -- Salafi Autodidacts -- Traditionalist Education -- The Teacher-Student Isnad -- Scholars as Heirs of the Prophets -- The Disenfranchisement of the Traditionalists -- The University System -- The Printing Press and New Media -- Reservations against Self-Learning -- Part II Islamic Law -- 4 Can Two Opposing Opinions Be Valid?: Legal Pluralism in Islam -- Certainty in Islamic Law -- Is Scripture Clear? -- Scriptural Interpretation -- Removing Ikhtilaf -- Why Do Scholars Differ? -- Differences as a Source of Mercy -- Consensus -- The (Im)Practicality of Consensus -- 5 Qur'an and Sunna or the Madhhabs? -- Defining Ijtihad and Taqlid -- Anti-Madhhabism -- Historical Validity of the Madhhabs -- Scholar or Scripture? -- Shifting Positions on Taqlid -- Part III Hadīth -- 6 The Pursuit of Authenticity: Reevaluating Weak ?adith -- Does Islam Need Weak ?adith? -- Different Approaches to Weak ?adith -- Do Weak ?adith Have Value? -- Dividing the ?adith Canon -- 7 Challenging Early Hadith Scholarship -- Reexamining the Collections of Bukhari and Muslim -- Traditionalist Criticisms of Albani's ?adith Methodology -- Relying on Abridgements -- Early vs. Late ?adith Scholarship -- Albani's Impact on Modern ?adith Studies.
Description based on publisher supplied metadata and other sources
Keywords: Islam -- 21st century; Islam -- 20th century; Islamic Modernism; Islamic Law; Salafīyah; Islamic fundamentalism; Islam-21st century; Electronic books